Rheological behavior of starch-based biopolymer mixtures in selected processed foods - Sarker, Md. Zaidul Islam; Abd Elgadir, Mohammed; Ferdosh, Sahena; Akanda, Mohammed Jahurul Haque; Aditiawati, Pingkan; Noda, Takahiro (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2013)
The objective of this review article is to investigate rheological behaviors of starch-based biopolymer mixtures in selected food systems. Numerous recently published studies on this subject were thoroughly screened and reviewed. This paper indicates rheological behaviors, which include viscoelasticity, texture, and viscosity, of starch-based biopolymer mixtures in selected food systems. It was found that starch-based biopolymer mixtures had different rheological behaviors that could affect the quality of processed foods. The main factors that affected rheological properties were the botanical sources of starches and the effect of mixing other biopolymers with starch. For instance, starch-based noodles prepared with potato starches were harder than noodles prepared with corn starch. Furthermore, the viscoelastic values of imitation cheese, which can be expressed by a storage modulus (G0) and a loss modulus (G00), increased with the addition of pregelatinized starch. In soup, another example of a starch-based biopolymer mixture, it was found that the presence of fenugreek polysaccharides (0.1–0.9% w/w) resulted in better development of viscoelastic properties with greater G0 and G00 compared with soups having no fenugreek polysaccharides added.